TERAPI GEL DAUN JAMBU BIJI UNTUK TRAUMA PUTING: EVALUASI NTS DAN IL-6 PADA IBU NIFAS - Husna, Dewi Asmaul; Wijayanti, Krisdiana; Susanto, Edy; Suwondo, Ari; Supriyana, Supriyana (Poltekkes Kemenkes Bandung, 2025)
A great and intelligent generation began during a child's golden period, as early stimulation and nutrition had a significant impact on brain development. During the early breastfeeding phase, approximately 34–94% of women experienced nipple trauma, which potentially reduced breastfeeding continuity. One non-pharmacological therapy alternative was the use of guava leaf gel, which was more practical and easy to apply. This study aimed to evaluate the effects of guava leaf gel on nipple trauma healing. The research was conducted at Midwife's Independent Practice Bidan Eka Setyowati, S.Tr.Keb, in Semarang from October to November 2024, using a quasi-experimental pretest-posttest design with a control group. The research sample consisted of a total of 30 postpartum mothers who experienced nipple fissures, selected through purposive sampling. Inclusion criteria consisted of postpartum mothers with healthy, single-born babies who breastfed and experienced grade 2 nipple trauma, while exclusion criteria included mothers with inverted nipples and babies with tongue-tie conditions. The intervention group received breast milk and guava leaf gel applications three times daily for five days, while the control group received only breast milk. Healing was measured using the Nipple Trauma Score (NTS). Data analysis used the Friedman and Wilcoxon tests. The average NTS in the control group was 1.60, while in the intervention group, it was 0.40. Statistical analysis showed a p-value of 0.000 (p<0.05), indicating a significant difference between pre- and post-intervention NTS scores in both groups. It was concluded that guava leaf gel effectively accelerated nipple trauma healing.